The post-repurchase announcement drift: an anomaly in disguise?. Issue 2 (9th February 2015) - Nguyen, Thanh T.; Sutton, Ninon K.; Pham, Dung (June)
Abstract : Purpose: – The purpose of this paper is to reexamine the stock price drifts after open-market stock repurchase announcements by differentiating actual repurchases from repurchase announcements and by controlling for the repurchasing firms' earnings improvement in the announcement year relative to the prior year. Design/methodology/approach: – The authors use the calendar-time method and matching method based on different criteria to calculate the post-announcement abnormal returns. Findings: – The results show that only firms actually repurchasing their shares exhibit a positive post-announcement drift. More importantly, the authors find that these repurchasing firms have the same post-announcement drift as their matching firms that have similar size and earnings performance but do not repurchase. This supports the argument that the post-repurchase announcement drift found in previous studies is not a distinct anomaly but the post-earnings announcement drift in disguise. Social implications: – The post-repurchase announcement drift found in previous studies is the post-earnings announcement drift in disguise. Originality/value: – The study shows that because high earnings performance positively relates to real repurchase activities, controlling for earnings performance in examining whether a drift occurs after repurchase announcements.